Appropriate global strategies for developing animal agriculture - Fitzhugh, H.A. (Alberta University, 1993)
Livestock play a vital role in economic Development-particularly as socities, evolve from subsistence agriculture into cash-based economies. On a global basis, animal products - meat, milk, eggs and fiber - constitute about 40 percent of the total value of agriculture output. This proportional contribution is about 50 percent in developed regions and 25 percent in developing regions. In developing regions, livestock provide major additional contributions to agriculture through draft power and manure for fuel and fertilizer. The growth markets for livestock products are in the developing regions. Improvements in livestock productivity are necessary to meet the substantial increase in demand for livestock products - especially in developing regions. However, it's neither appropriate nor sustainable to achieve these increase by mining the fragile natural resource base at the expense of futur generations. It is here that there is greatest need for research and technology transfer. Increasingly global strategies for livestock Development must consider the environmental impact and the inter-regional economics of production and marketing. Improved livestock productivity supporting economic Development and sustainable rational resource management are not incompatible goals. Inter-regional trade and market Development must consider differences in comparative and competitive advantage, which often do not coincide. Subsidies, price controls, trade barriers and other factors can neutralize comparative advantage of developing countries for low cost livestock production. Animal agriculture can be a positive factor in long term, sustainable agriculture by incorporating adequate economic returns to livestock farmers; maintainance of natural resources and productivity; minimal adverse environmental effects; optimial production with minimal external inputs; and satisfaction of food income as well as social needs.